Association of clinical outcomes and the predictive value of T lymphocyte subsets within colorectal cancer patients - Yuan, Chaofeng; Huang, Jiannan; Li, Haitao; Zhai, Rongnan; Zhai, Jinjing; Fang, Xuedong; Wu, Yuanyu (Frontiers in Surgery, 2023)
This clinical study systematically describes and analyzes the association of CD4+ and CD8+ T-lymphocyte content and CD4+/CD8+ T-lymphocyte ratio with colorectal cancer differentiation, clinical pathological stage, Ki67 expression, T-stage, N-stage, carcinoembryonic antigen (CEA) content, nerve and vascular infiltration, and other clinical features, as well as preoperative and postoperative trends. After formulating strict inclusion and exclusion criteria to screen patients, preoperative and postoperative flow cytometry and postoperative pathology reports from standard laparoscopic surgery were assessed. We found that a high CD4+ T-lymphocyte content in peripheral blood and a high CD4+/CD8+ ratio were associated with better tumor differentiation, an earlier clinical pathological stage, lower Ki67 expression, shallower tumor infiltration, a smaller number of lymph node metastases, a lower CEA content, and a lower likelihood of nerve or vascular infiltration (P < 0.05). However, a high CD8+ T-lymphocyte content indicated an unpromising clinical profile. After effective surgical treatment, the CD4+ T-lymphocyte content and CD4+/CD8+ ratio increased significantly (P < 0.05), while the CD8+ T-lymphocyte content decreased significantly (P < 0.05). Further, we comprehensively compared the merits of CD4+ T-lymphocyte content, CD8+ T-lymphocyte content, and CD4+/CD8+ ratio in predicting the clinical features of colorectal cancer by means of receiver operating characteristic curves. We then combined the CD4+ and CD8+ T-lymphocyte content to build logistic regression models and predict major clinical characteristics. We compared these models with the CD4+/CD8+ ratio to explore their advantages and disadvantages in predicting the clinical features of colorectal cancer. Our results provide a theoretical basis for the future screening of effective markers in reflecting and predicting the progression of CRC.